2019
DOI: 10.1021/acsabm.9b00833
|View full text |Cite
|
Sign up to set email alerts
|

Polyionic Complexed Antibacterial Heparin–Chitosan Particles for Antibiotic Delivery

Abstract: Efficient delivery of antibacterial agents directly to sites of tissue injury faces challenges such as poor drug stability and fast degradation by biological mechanisms. Biocompatible nanocarrier systems can help sustain and control the delivery of antibacterial compounds while reducing the chances of antibacterial resistance or accumulation in unwanted tissues. In this study, we report the application of tailored polyionic particles via ionic interactions between negatively charged heparin and positively char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 65 publications
0
15
0
2
Order By: Relevance
“…Generally, the contact angles increased with chitosan as the terminal layer and decreased with heparin as the terminal layer, which is consistent with previous literature [ 18 ]. The contact angle slightly decreased as layer increased, which demonstrated that all of the surfaces are hydrophilic and reflect the antifouling characteristics of the multilayer films [ 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Generally, the contact angles increased with chitosan as the terminal layer and decreased with heparin as the terminal layer, which is consistent with previous literature [ 18 ]. The contact angle slightly decreased as layer increased, which demonstrated that all of the surfaces are hydrophilic and reflect the antifouling characteristics of the multilayer films [ 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption of PTH in the presence of BSA on polysaccharide-based multilayer films in PBS was investigated because BSA was identified as one of the most important types of adsorbed proteins in blood–material interaction. Jin et al revealed that polydopamine coated polyurethane film with heparin and carboxymethyl chitosan modification showed a significant decrease of protein adsorption and enhancement of hemocompatibility and antibacterial properties in comparison with polyurethane film [ 19 , 21 ]. Heparin/chitosan complex materials and modification have been widely evidenced to increase hydrophilicity, decrease BSA and fibrinogen adsorption and enhance blood compatibility [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 17 ] Chitosan is primarily sourced as a shellfish byproduct, as was used in this study, however, newer high purity fermentation sourced chitosan has now become available to reduce sourcing concerns. [ 18 ] The ability to perform amine targeted bioconjugations to the chitosan polymer backbone allows straightforward covalently tethering of PFCs [ 12 ] to provide stability and confirming the ability to manipulate and utilize PFCs in new applications.…”
Section: Introductionmentioning
confidence: 99%